Cloning, expression, purification, crystallization and preliminary X-ray diffraction studies of N-acetylneuraminate lyase from methicillin-resistant Staphylococcus aureus - North, Rachel A. (International Union of Crystallography, 2013)

(untitled)
The enzyme N-acetylneuraminate lyase (EC 4.1.3.3) is involved in the metabolism of sialic acids. Specifically, the enzyme catalyzes the retro-aldol cleavage of N-acetylneuraminic acid to form N-acetyl-d-mannosamine and pyruvate. Sialic acids comprise a large family of nine-carbon amino sugars, all of which are derived from the parent compound N-acetylneuraminic acid. In recent years, N-acetylneuraminate lyase has received considerable attention from both mechanistic and structural viewpoints and has been recognized as a potential antimicrobial drug target. The N-acetylneuraminate lyase gene was cloned from methicillin-resistant Staphylococcus aureus genomic DNA, and recombinant protein was expressed and purified from Escherichia coli BL21 (DE3). The enzyme crystallized in a number of crystal forms, predominantly from PEG precipitants, with the best crystal diffracting to beyond 1.70 Å resolution in space group P2(1). Molecular replacement indicates the presence of eight monomers per asymmetric unit. Understanding the structural biology of N-acetylneuraminate lyase in pathogenic bacteria, such as methicillin-resistant S. aureus, will provide insights for the development of future antimicrobials.